Understanding deviance : a guide to the sociology of crime and rule-breaking - Downes, David M.; Rock, Paul Elliott (Oxford : Oxford Univ Press, 2011)
'Understanding Deviance' provides an indispensable guide to the major themes and theories which have come to form the sociology of crime and deviance, from their origins in the research of the University of Chicago sociology department in the 1920s to the most recent work in cultural criminology.
Includes bibliographical references (p. [361]-393) and index.
Keywords: Deviant behavior; Crime -- Sociological aspects